2006
DOI: 10.1007/s00432-006-0165-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor SOX2 up-regulates stomach-specific pepsinogen A gene expression

Abstract: These data suggest that SOX2 plays an important role in regulation of pepsinogen A, and ectopic expression of SOX2 may be associated with abnormal differentiation of colorectal cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Our present results may therefore be similar to the normal cell differentiation process in the stomach. Furthermore, SOX2 has been found to upregulate the expression levels of gastric differentiation markers, MUC5AC and pepsinogen A (Li et al, 2004;Tani et al, 2007). These data, combined with the findings for antiproliferation effects of SOX2 in gastric epithelial cell lines, suggest that SOX2 may control the gastric epithelial cells differentiating into mature cells and its disruption may cause continual dividing, eventually leading to gastric cancer.…”
Section: Roles Of Sox2 In Gastric Carcinogenesismentioning
confidence: 83%
See 1 more Smart Citation
“…Our present results may therefore be similar to the normal cell differentiation process in the stomach. Furthermore, SOX2 has been found to upregulate the expression levels of gastric differentiation markers, MUC5AC and pepsinogen A (Li et al, 2004;Tani et al, 2007). These data, combined with the findings for antiproliferation effects of SOX2 in gastric epithelial cell lines, suggest that SOX2 may control the gastric epithelial cells differentiating into mature cells and its disruption may cause continual dividing, eventually leading to gastric cancer.…”
Section: Roles Of Sox2 In Gastric Carcinogenesismentioning
confidence: 83%
“…Ten human gastric cancer cell lines (MKN7, MKN45, MKN74, NUGC3, NUGC4, GCIY, TGBC11TKB, KATOIII, HSC58 and HSC59) were obtained as described previously (Tani et al, 2007). Rat gastric epithelial cell line OUMS37 was obtained from Dr Masayoshi Namba (Okayama University Medical School, Japan) (Pu et al, 1999).…”
Section: Cell Lines and Tissue Samplesmentioning
confidence: 99%
“…32 SOX2 contributes to the development of foregut-derived organs, such as the esophagus and stomach, 33,34 and controls the expression of pepsinogen A and Muc5ac. 35,36 The expression of SOX2 is downregulated during the progression from incomplete to complete intestinal metaplasia. 37 In addition, it was suggested that SOX2 can function as a tumor suppressor by regulating the cell cycle and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Recently, increasing evidence suggests that factors involved in cell pluripotency and self-renewal, key characteristics of stem cells, are implicated in cancer biology. [11][12][13][14][15][16][17][18][19][20][21][22][23] Specifically, the existence of human ovarian cancer-initiating cells with stemness properties and enhanced resistance to cisplatin and paclitaxel has been reported. 17 Indeed, since the isolation of human embryonic stem cells (ESCs), 24 significant interests have been generated in science and medicine because of their therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%